The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1063/1.365847
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of hydrogen-passivated silicon surfaces by scanning near-field optical lithography using uncoated and aluminum-coated fiber probes

Abstract: Optically induced oxidation of hydrogen-passivated silicon surfaces using a scanning near-field optical microscope was achieved with both uncoated and aluminum-coated fiber probes. Line scans on amorphous silicon using uncoated fiber probes display a three-peak profile after etching in potassium hydroxide. Numerical simulations of the electromagnetic field around the probe–sample interaction region are used to explain the experimental observations. With an aluminum-coated fiber probe, lines of 35 nm in width w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…The probe-to-sample separation is approximately 5-10 nm and controlled at a constant-distance mode during scanning. The observed three-peak profile is consistent with a numerical finding by simulating the electromagnetic field around the probe-sample interaction region [14]. As compared, the results obtained from the uncoated probe to the pattern shown in Fig.…”
Section: Materials Modificationsupporting
confidence: 88%
See 4 more Smart Citations
“…The probe-to-sample separation is approximately 5-10 nm and controlled at a constant-distance mode during scanning. The observed three-peak profile is consistent with a numerical finding by simulating the electromagnetic field around the probe-sample interaction region [14]. As compared, the results obtained from the uncoated probe to the pattern shown in Fig.…”
Section: Materials Modificationsupporting
confidence: 88%
“…A proper explanation of the size enlargement due to light illumination can be that the induced electric field near the probe-sample region is enhanced by the illumination and resulted in stronger hydrogen (H) depassivation (desorption) and, in turn, to have larger patterned areas or oxidized sizes. The electric field enhancement by the SNOM light illumination should be consistent with the numerical simulation of the electromagnetic field similar to that reported by Madsen et al [14] mentioned earlier. Moreover, Herndon et al [15] also found that the probe oscillation amplitude greatly affects the dimensions of patterns generated and reported a patterned a-Si:H surface without light exposure shown in Fig.…”
Section: Article In Presssupporting
confidence: 75%
See 3 more Smart Citations